Crystallization kinetics and enhanced dielectric properties of free standing lead-free PVDF based composite films - Meng, Nan; Mao, Rui; Tu, Wei; Odolczyk, Katarzyna; Zhang, Qi; Bilotti, Emiliano; Reece, Michael J. (Elsevier, 2017)
Ferroelectric composites, integrating dielectric ceramic fillers with mechanically flexible polymers, are promising materials for flexible electronic applications. Plenty of research has demonstrated the enhanced dielectric and ferroelectric properties of composite materials. However, the mechanisms responsible for these enhancements are not completely understood. Herein, we used typical dielectric materials, poly(vinylidene fluoride) (PVDF) and BaTiO3 (BTO), to study the effect of a dielectric filler on the crystallization, phase transformation and dielectric properties of PVDF. The crystallization of β-PVDF was not affected by the presence of BTO particles, but small amounts of BTO (<3 vol %) made PVDF crystallize into larger spherulites. This is linked to crystallization kinetic studies, which showed that BTO acted as a nucleation agent for large full ring banded spherulites when its content was less than 1 vol %. Furthermore, solid state drawing in the presence of BTO particles promoted the formation of β-PVDF with more pronounced preferred crystalline orientation at high drawing temperatures (120 °C). The dielectric and ferroelectric properties were enhanced with BTO filling. The 100 °C oriented drawn PVDF tape exhibited a dielectric permittivity of 14 (100 Hz) and remnant polarization of 0.080 C/m2 (10 Hz), which increased to 23 and 0.095 C/m2, respectively, after filling with 5 vol % BTO; neither resulting in high dielectric loss tangent (∼0.02) nor obvious current leakage. Moreover, the coercive field decreased from 80 to 50 kV/mm with increasing BTO content from 0 to 5 vol %.
Keywords: PVDF composites; Crystallization kinetics; Dielectric